Uma mistura de experiências: extensão universitária em duas regiões do México - Ejea Mendoza, León Tomás (Universidad Nacional del Litoral, 2021)
In this article, we present how the university extension programs of the Higher Education Institutions of two geographical regions of Mexico are related to their surroundings on environmental issues: the Region of the State of Chiapas and the region called the Riviera Maya. It can be said that in Chiapas, with its strong composition of the communitarian indigenous population, there is a tendency towards an ecological approach. For its part, the Riviera Maya, as a tourist centre of international luxury, tends towards the economistic approach. In this sense, we show that the forms of intervention and relationship of higher education institutions in Mexico with their surroundings present a great diversity of options that allow us to assert that it is a true melting pot of experiences.